PERUBAHAN PERMUKIMAN PENDUDUK KECAMATAN SOMBA OPU KABUPATEN GOWA TAHUN 1993 SAMPAI DENGAN TAHUN 2018 - Irnayani, Mayasari (UNIVERSITAS NEGERI MAKASSAR, 2019)
ABSTRACTThis research aims to find out and analyze changes in land area of settlement, land use and settlements turns into a factor that affected it. The method used is the analysis of remote sensing and descriptive analysis. The results showed that extensive settlements in 1993 was 307.03 Ha and in 2018 is 1653.34 Ha. Then it can be inferred the vast increase of land due to land use change shrub, open land, moor/fields, ricefield, and the body of water into the neighborhoods with the factors that affect that is the high rate of population growth amounted to 5.74 percent and affordable land prices as well as the completeness of the infrastructure in Somba Opu.